2011
DOI: 10.1002/eqe.1163
|View full text |Cite
|
Sign up to set email alerts
|

Free‐field rotations during earthquakes: Relevance on buildings

Abstract: Soil rotations around horizontal axes, during an earthquake, are studied through records collected by closely spaced arrays of strong motion accelerometers. The cross power spectrum of accelerations at nearby stations has been generally utilized to describe the spatial distribution of the motion. A number of cross spectra have been obtained during the training of these arrays. To take profit of these elaborations, a mathematical relation is established between the cross power spectrum and the power spectrum of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 38 publications
(67 reference statements)
0
10
0
Order By: Relevance
“…Newmark’s study paved the way for more sophisticated solutions (examples among others: [ 18 , 76 , 85 , 86 , 87 ]), from horizontal motion recorded in a free field to the generation of products (such as synthetic seismograms and response spectra) for designing structures. Numerical studies, whether based on the analysis of equivalent static lateral forces (force applied at a distance—eccentricity—from the centre of stiffness) or dynamic analysis, conclude that design forces increase due to accidental eccentricity [ 60 ].…”
Section: Accidental Eccentricitymentioning
confidence: 99%
See 1 more Smart Citation
“…Newmark’s study paved the way for more sophisticated solutions (examples among others: [ 18 , 76 , 85 , 86 , 87 ]), from horizontal motion recorded in a free field to the generation of products (such as synthetic seismograms and response spectra) for designing structures. Numerical studies, whether based on the analysis of equivalent static lateral forces (force applied at a distance—eccentricity—from the centre of stiffness) or dynamic analysis, conclude that design forces increase due to accidental eccentricity [ 60 ].…”
Section: Accidental Eccentricitymentioning
confidence: 99%
“…In asymmetric structures, when Ty increases and Ω decreases, the influence of static eccentricity increases, and the effect of torsional ground motion can be ignored for tall asymmetric buildings. Castellani et al [ 87 ] concluded that the contribution of the rotational component on the response of the structure is more significant for a high-rise building (based on a numerical comparison between a low-rise building Ty=0.48s and a flexible building Ty = 1.56 s), which is a difference that can exceed 20%. They also showed that the higher modes could be neglected and that only the low-frequency portion of the response spectra induces significant rotational excitation.…”
Section: Experimental and Numerical Observation Of Torsionmentioning
confidence: 99%
“…Extending the response spectrum to rotational ground motion adds a similarly useful tool when considering rotational ground motions in seismic design. Similarly to the translational response spectrum, the rotational response spectrum represents the peak rotational acceleration of a single degree of freedom rotational oscillator as a function of natural period and damping ratio, excited by a prescribed rotational ground acceleration [46].…”
Section: Engineering Applicationsmentioning
confidence: 99%
“…On the other hand, ground motion rotations are rarely considered in site effects studies, due to difficulties involved in measuring rotational motions and strains and because of a widespread preconception in the seismological community that rotational motions are insignificant (Lee et al 2009). In the earthquake engineering community instead, the ground rotational motion gained interest (Lee and Trifunac 1985;Castellani et al 2012), since the travelling wave effect was recognized by Newmark (1969) and it is today accounted for in building codes under the term accidental eccentricity (Anagnostopoulos et al 2015). While the research regarding the relevance of ground motion rotations is still undergoing (Guidotti et al 2018), in the present work we investigate the possibility of topography-induced rotations around the vertical axis (torsional motion).…”
Section: Introductionmentioning
confidence: 99%